The neuromechanics of the soleus for fall prevention in aging - Fletcher, Jared R.; Strzalkowski, Nicholas D. J. (Frontiers in Physiology, 2026)
Falls are a leading cause of injury-related hospitalization, morbidity, and mortality in older adults, with impaired postural control serving as a key predictor of fall risk. The triceps surae, and particularly the soleus, plays a central role in maintaining upright stance by generating continuous plantarflexion moments that stabilize the body’s center of mass. This mini-review summarizes evidence for the neuromechanical contributions of the soleus to postural stability and how these functions decline with age. Mechanically, the soleus acts as a brace for balance, providing sustained torque through fatigue-resistant type I fibers and a compliant Achilles tendon that buffers perturbations and contributes to ankle stiffness. Age-related reductions in tendon stiffness and rate of torque development compromise these stabilizing properties, increasing fall susceptibility. When passive stiffness is insufficient, the soleus compensates through active contraction, trading energy cost of activation for joint stability. Reflexively, the soleus serves as a stabilizer of balance through strong coupling to spinal, cutaneous, vestibular, and transcortical pathways that rapidly adjust muscle activation in response to perturbations. These reflex mechanisms also degrade with aging, leading to delayed, less adaptable responses. Together, age-related mechanical and neural deterioration reduce the soleus’ ability to sustain balance and contribute to fall recovery. Preserving soleus strength, tendon stiffness, and reflex adaptability through targeted neuromuscular and perturbation-based training may represent an underrecognized but effective strategy to mitigate fall risk and maintain postural control in older adults.